Evaluation of the Implementation of the Annual Conference of Education Culture and Technology (ACECT) 2022 Using the Model Outcome-Based Evaluation (OBE) - Adiyana Adam; Arif Rahman Fitrianto; Abdurrahman Hi Usman; Sahjad M Aksan (Education Specialist, 2024)
This study evaluates the implementation of the Annual Conference of Education, Culture, and Technology (ACECT) 2022 using the Outcome-Based Evaluation (OBE) model. This evaluation aims to measure the results achieved, identify obstacles faced, and provide recommendations for future improvements. The evaluation results showed that the conference succeeded in improving the quality and quantity of scientific publications, with 48 papers published in Sinta accredited journals and 120 other papers in the Proceeding e-Book. Participant satisfaction with the organization of the conference reached 85%, although there were some obstacles such as limited presentation time, technical problems, and the length of the paper assessment process. Expert opinions emphasized the importance of adequate time allocation, thorough technical preparation, and an efficient evaluation process. Overall, the conference made a positive contribution to the participants' academic and professional development, and enhanced the academic reputation of the participating institutions.